Współpraca samorządów powiatów w zakresie ochrony zdrowia na podstawie porozumienia administracyjnego - Gałuszka, Krzysztof (Cooperation of a District Authorities in the Field of Health Care on the Basis of Administrative Agrement., 2006)
Following the decentralization of the public services, the tasks relating to health care and promotion, have been imposed on the district authorities. Regarding the diversification of the districts and the nature of health care services, the inter-district cooperation is necessary during the process of its effective performance. The paper treats on the issue of using the administrative agreement, as a form of cooperation among district authorities in the field of health care.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1103, s. 153-164